2022
DOI: 10.1186/s12893-022-01709-6
|View full text |Cite
|
Sign up to set email alerts
|

Is sentinel lymph node biopsy without frozen section in early stage breast cancer sufficient in accordance with ACOSOG-Z0011? A retrospective review from King Chulalongkorn Memorial Hospital

Abstract: Background In 2021, there is an increased global trend for sending sentinel lymph node biopsy (SLNB) specimens for permanent section (PS) without intraoperative frozen sections (FS). This pilot study conducted in Thailand determines the re-operation rate for SLNB without FS. Method We retrospectively reviewed 239 SLNB cases without FS at King Chulalongkorn Memorial Hospital from April 2016 to April 2021. The patients were diagnosed with primary inv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…On the other hand, the reduction of the operative time may allow one or two more procedures to be scheduled every day in the surgical theatre, with considerable economical savings and boosted clearance of the waiting list. The reduction in health care costs associated with this change in management of SLNBs has also been highlighted by others (20,(36)(37)(38)(39)(40). However, others reported opposite conclusions, claiming an increase in costs with the use of PS-SLNB in consideration of a higher reoperation rate (41).…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, the reduction of the operative time may allow one or two more procedures to be scheduled every day in the surgical theatre, with considerable economical savings and boosted clearance of the waiting list. The reduction in health care costs associated with this change in management of SLNBs has also been highlighted by others (20,(36)(37)(38)(39)(40). However, others reported opposite conclusions, claiming an increase in costs with the use of PS-SLNB in consideration of a higher reoperation rate (41).…”
Section: Discussionmentioning
confidence: 80%
“…However, recent studies suggest that iFS may be unnecessary in early-stage breast cancer patients, where tumor size and axillary lymph node status can be used as prognostic factors [8,17]. This trend has already been observed in lumpectomy cases, where iFS has been found to confer minimal diagnostic value, in accordance with the ACOSOG criteria [13,14]. A recent randomized controlled trial conducted by The European Institute of Oncology of Milan (SOUND trial) even con rmed the safety of omitting SLNB in well-selected early-stage breast cancer patients who were treated with breast-conserving surgery and had no evidence of axillary node involvement by clinical and ultrasound evaluation [18].…”
Section: Discussionmentioning
confidence: 98%
“…Our previous studies demonstrated that reoperation rates in SLNBs without iFS in breast conserving surgery patients was no different than that in SLNBs with iFS [12,13]. However, the recent NCCN guidelines permitting a few positive SLNs in mastectomy patients have raised questions about the necessity of iFS in this context.…”
Section: Introductionmentioning
confidence: 99%